AN ANALYSIS OF PERSONAL DEIXIS IN SHORT STORY “THE GIFT OF THE MAGI” - Eka Fajar Rahmani; Putri Eka Meitasari; Luwandi Suhartono (Jurnal Ilmiah Spectral, 2023)
This research aims at describing and interpreting the deictic expressions of personal deixis in the Gift of the Magi short story. This research specifically examined the appearance of personal deixis and the interpretations of the context. The data's primary source was the short story's utterances and sentences. In conducting the research, the researchers employed a descriptive quantitative design where the primary data was in the form of percentages of personal deixis that appeared in the short story, followed by their interpretation. From the analysis, there found 231 personal deixes in the short story consisting of 43 first-person deixes (18,61%), 14 second-person deixis (6,06%), and 174 third-person deixes (75,32%). Referring to these results, it was interpreted that the author of the Gift of the Magi told the story from his point of view to bring the readers to objectively understand the characters, conflicts, and ideas of the story. The author also would like to project his identity as he knows the whole story and the characterization of each character, including thoughts, feelings, and opinions. By having so, the readers get much help in grabbing the essence of the story completely. In short, understanding the role of personal deixis in a short story is essential to comprehend the detail of the story.